Superparamagnetic iron oxide nanoparticles: magnetic nanoplatforms as drug carriers - Wahajuddin (Dove Medical Press, 2012)
Wahajuddin,1,2 Sumit Arora21Pharmacokinetics and Metabolism Division, CSIR-Central Drug Research Institute, Lucknow, Uttar Pradesh, 2Department of Pharmaceutics, National Institute of Pharmaceutical Education and Research, Rae Bareli, IndiaAbstract: A targeted drug delivery system is the need of the hour. Guiding magnetic iron oxide nanoparticles with the help of an external magnetic field to its target is the principle behind the development of superparamagnetic iron oxide nanoparticles (SPIONs) as novel drug delivery vehicles. SPIONs are small synthetic γ-Fe2O3 (maghemite) or Fe3O4 (magnetite) particles with a core ranging between 10 nm and 100 nm in diameter. These magnetic particles are coated with certain biocompatible polymers, such as dextran or polyethylene glycol, which provide chemical handles for the conjugation of therapeutic agents and also improve their blood distribution profile. The current research on SPIONs is opening up wide horizons for their use as diagnostic agents in magnetic resonance imaging as well as for drug delivery vehicles. Delivery of anticancer drugs by coupling with functionalized SPIONs to their targeted site is one of the most pursued areas of research in the development of cancer treatment strategies. SPIONs have also demonstrated their efficiency as nonviral gene vectors that facilitate the introduction of plasmids into the nucleus at rates multifold those of routinely available standard technologies. SPION-induced hyperthermia has also been utilized for localized killing of cancerous cells. Despite their potential biomedical application, alteration in gene expression profiles, disturbance in iron homeostasis, oxidative stress, and altered cellular responses are some SPION-related toxicological aspects which require due consideration. This review provides a comprehensive understanding of SPIONs with regard to their method of preparation, their utility as drug delivery vehicles, and some concerns which need to be resolved before they can be moved from bench top to bedside.Keywords: superparamagnetic iron oxide nanoparticles, SPIONs, targeted delivery, coating, functionalization, targeting ligands, toxicity